Sharing Knowledge Through Publishing Research Work in Indexed Journals: A Vision of Malaysian Private Universities - Hosen, Mosharrof (Animo Repository, 2020)
Policymakers are overwhelmingly worried about reinforcing new trends for academics’ knowledge sharing through publishing research work in indexed journals. By being the first, this study investigates the issue from the behavioral perspective along with perceived trust construct while inundating previous studies discovered from different factors, including technological, environmental, and cultural. A total of 315 valid responses were received from Malaysian private universities’ academics through a self-administrated questionnaire survey. Covariance-based structural equation modeling was implemented to test the hypotheses. The results indicate that perceived trust has a significant positive impact on attitude, but a negative effect on intention. Furthermore, attitude and subjective norms can positively stimulate academics’ intention to publish a paper. Likewise, perceived behavioral control has a positive and negative impact on academics’ intention and publication behavior, respectively. Thus, a positive rapport had been established between intention and actual behavior. In lieu of these, the insightful results received from this study would help policymakers design a successful behavioral intervention program in higher educational institutions settings to accelerate academics’ knowledge sharing. Future directions and policy implications are discussed accordingly.